Radiogenomic signatures reveal multiscale intratumour heterogeneity associated with biological functions and survival in breast cancer - Ming Fan (Nature Portfolio, 2020)
Tumours are made up of heterogeneous subclones. Here, the authors show using breast cancer imaging and gene expression datasets that these subclones can be inferred by the deconvolution of gene expression data, mapped to MRI derived radiogenomic signatures and used to estimate prognosis.